1998
DOI: 10.1109/22.668642
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional fiber-optic microwave links based on remote heterodyne detection

Abstract: Abstract-The multifunctionality of microwave links based on remote heterodyne detection (RHD) of signals from a dual-frequency laser transmitter is discussed and experimentally demonstrated in this paper. Typically, direct detection (DD) in conjunction with optical intensity modulation is used to implement fiber-optic microwave links. The resulting links are inherently transparent. As opposed to DD links, RHD links can perform radio-system functionalities such as modulation and frequency conversion in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 24 publications
(38 reference statements)
0
39
0
Order By: Relevance
“…It is found that the center of the stable-locking range is shifted toward the lower frequency from the SL lasing frequency as the injection ratio increases. Similar dependence of the stablelocking range on the injection ratio has been shown from the analysis based on Lang's equations [8].…”
Section: Principle Of the Proposed Methodsmentioning
confidence: 53%
See 1 more Smart Citation
“…It is found that the center of the stable-locking range is shifted toward the lower frequency from the SL lasing frequency as the injection ratio increases. Similar dependence of the stablelocking range on the injection ratio has been shown from the analysis based on Lang's equations [8].…”
Section: Principle Of the Proposed Methodsmentioning
confidence: 53%
“…In order to investigate the effect of the presence of the multiple ML sidebands on the SL spectral characteristics, we have adopted Lang's equations based on the complex electrical field [8]. Then, we have extended those equations representing the laser diode (LD) under multiple lights as follows.…”
Section: Principle Of the Proposed Methodsmentioning
confidence: 99%
“…Due to its resistance to handling damage, large core graded index polymethylmethacrylate (PMMA) plastic optical fiber (GI-POF) is a preferred choice for in-home networking [3]. This paper demonstrates for the first time, using remote heterodyning technique (RHD) [4], to deliver 5 Gbit/s data over a combination of SMF and MMF-POF cables. The combination of SMF and MMF utilization for mm-wave transmission is highly favorable but yet challenging due to the high bandwidth impairments induced by the MMF-POF material.…”
Section: Introductionmentioning
confidence: 98%
“…Several techniques for distributing and generating microwave signals via optical fiber exist. The techniques may be classified into two main categories namely Intensity ModulationDirect Detection (IM-DD) and Remote Heterodyne Detection (RHD) techniques [3]. In such systems, it is desirable to achieve better receiver sensitivities, higher dynamic ranges, and lower nonlinear distortions.…”
Section: Introductionmentioning
confidence: 99%